The “two faces” of water crisis:: scarcity and water access depoliticisation in Rio de Janeiro Metropolitan Region - Quintslr, Suyá (Sustainability in Debate, 2018)
This paper examines the water crisis’ discourse during 2014-2015 by discussing its legitimation strategies and part in excluding the issue of unequal access to water resources from decision-making. To this end, I employ two theoretical perspectives. Firstly, by adopting a constructionist approach, the paper makes a case that the construction of environmental problems involves both material and symbolic dimensions. Secondly, is the "invisible face of power", or the elites’ ability to mobilize social values and the bias of the political system to keep certain issues off the agenda. Data collection and examination were based on direct observation, and media and official document analysis. The results support the claim that a crisis-centered discourse has framed the water supply issue as a quantitative problem in detriment to the distributive realm, and has legitimized major infrastructure works in order to increase water production.